Ocean bottom hydrophone sgy-files of wide-angle seismic data of profile ATLANTIS-I, 31N Central Atlantic - Ingo Grevemeyer; César R Ranero; Arantza Ugalde; Manel Prada (PANGAEA, 2024)
Wide-Angle Seismic (WAS) data acquired across ATLANTIS-I profile in 2022 at 31N Central Atlantic. The seismic data were recorded with 22 ocean bottom hydrophones (OBH) from GEOMAR (Germany), deployed every ~8 km along the transect. Processing of OBH data involved receiver relocation using an in-house Metropolis-Hasting grid-search algorithm, a Wiener predictive error filtering, and a band pass filter.